Development of tactile floor plan for the blind and the visually impaired by 3D printing technique - Urbas, Raša; Pivar, Matej; Stankovič Elesini, Urška (Journal of Graphic Engineering and Design, 2016)
The aim of the research was to produce tactile floor plans for blind and visually impaired people for the use in the museum. For the production of tactile floor plans 3D printing technique was selected among three different techniques. 3D prints were made of white and colored ABS polymer materials. Development of different elements of tactile floor plans, as well as the problems and the solutions during 3D printing, are described in the paper.